PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PKN DI KELAS XI TGP SMK NEGERI 1 BUNYU - RISMADAMAYANTI RISMADAMAYANTI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
This classroom action research aims to determine the increase in student participation through the application of the Think Pair and Share cooperative learning model in Civics subjects in Class XI TGP SMK Negeri 1 Bunyu. This research was conducted in two cycles. Each cycle uses the Think Pair and Share cooperative learning model by continuously improving the quality of group learning implementation. Each group consists of 2 people, where each study group is given the same problem, in accordance with the learning objectives that are completed with their partner and then present the results of the discussion in front. The teacher's role as a facilitator, manager, motivator, and consultant is very important in implementing the learning process in the classroom so that it is successful. From the results of observations, students have diverse backgrounds and ways of learning. For this reason, teachers must also be able to make variations in learning models and methods so that they will motivate students to learn. Learning that is fun and gives space for students to explore their abilities is the right way to maximize abilities and learning outcomes as well as students' learning motivation. This can be seen from the average classical learning outcomes in cycle I at number 55 and in cycle II it reaches 89.12 with a complete learning percentage reaching 100%. In addition to learning outcomes in cycle II there is also an increase in student activity and motivation. In Cycle I the activity of students was only at 68.75% and in Cycle II there was an increase of 85.62%. The results of the acquisition in cycle II have reached the minimum expected by the author, namely 75%. The results of this action research are expected to be an incentive for teachers to make this research a reference and invite other teachers to carry out action research with other themes in an effort to improve teacher professionalism. ABSTRAKPenelitian tindakan kelas ini bertujuan untuk mengetahui peningkatan partisipasi siswa melalui penerapan model pembelajaran kooperatif tipe Think Pair and Share pada mata pelajaran PKn di Kelas XI TGP SMK Negeri 1 Bunyu. Penelitian ini dilaksanakan dalam dua siklus. Setiap siklus menggunakan model pembelajaran kooperatif tipe Think Pair and Share dengan senantiasa meningkatkan kualitas pelaksanaan pembelajaran kelompok. Setiap kelompok terdiri atas 2 orang, dimana masing-masing kelompok belajar diberikan masalah yang sama, sesuai dengan tujuan pembelajaran yang diselesaikan bersama pasangannya lalu mempresentasekan hasil diskusi didepan. Guru berperan sebagai fasilitator, manajer, motivator, maupun konsultan sangat penting dalam pelaksanaan proses pembelajaran di kelas agar berhasil. Dari hasil pengamatan peserta didik memiki latar belakang dan cara belajar yang beragam untuk itu guru juga harus bisa membuat variasi model dan metode pembelajaran sehingga akan memberi motivasi kepada peserta didik untuk belajar. Pembelajaran yang menyenangkan dan memberi ruang kepada peserta didik untuk mengeksplor kemampuannya adalah cara tepat untuk memaksimalkan kemampuan dan hasil belajar serta motivasi belajar peserta didik. Hal ini dapat dilihat dari rata-rata hasil belajar klasikal siklus I pada angka 55 dan pada siklus II mencapai 89,12 dengan prosentase ketuntasan belajar mencapai 100%.Selain hasil belajar pada siklus II juga terjadi peningkatan aktifitas dan motivasi peserta didik. Pada Siklus I keaktifan peserta didik hanya pada angka 68,75% dan pada siklus II terjadi peningkatan yakni 85,62%. Hasil perolehan pada siklus II ini sudah mencapai batas minimal yang diharapkan penulis yakni 75%. Hasil penelitian tindakan ini diharapkan dapat menjadi pendorong bagi guru-guru untuk menjadikan acuan penelitian ini dan mengajak guru yang lain untuk melaksanakan penelitian tindakan dengan tema yang lain dalam upaya meningkatkan profesionalisme guru.